ANALYSIS OF METAPHORS IN TERM OF SLAVERY RESISTANCE AS REFLECTED IN BOB MARLEY’S SONGS LYRIC; REDEMPTION SONG AND BUFFALO SOLDIER (English Department, Faculty of Languages and Arts, Universitas Negeri Semarang, 2014)
This study is attempted to analyze metaphor in Bob Marley’s selected lyrics; entitled Redemption Song and Buffalo Soldier. The problems of the study are 1) what types and meanings of each metaphor found in Bob Marley’s selected lyrics? 2) How those metaphorical expressions intensify slavery resistance as the content of the songs? The aim of this research is to find out the types of metaphors used in those lyrics and to understand the meanings of words, phrases or sentences contained the data. To achieve the objectives of the study, I used qualitative descriptive research and semantics as the approach in order to interpret the meanings. I collected the data from the songs lyrics, then classified them into types of metaphor. Based on the theories provided, the data were analyzed one by one to know the types of metaphor used and the meaning of them. Metaphorical expressions found mostly in the songs lyrics are structural metaphor and ontological metaphor. In the beginning, the metaphorical expressions were explained in their literal meanings, so they could show the influence of using metaphor in the phrase or sentence. Through songs lyrics as the object of my analysis, it could be concluded that those songs lyrics generally contained metaphorical expressions.